2015
DOI: 10.1186/s12890-015-0087-y
|View full text |Cite|
|
Sign up to set email alerts
|

Ventilator-associated Pneumonia caused by commensal oropharyngeal Flora: a retrospective Analysis of a prospectively collected Database

Abstract: BackgroundThe significance of commensal oropharyngeal flora (COF) as a potential cause of ventilator-associated pneumonia (VAP) is scarcely investigated and consequently unknown. Therefore, the aim of this study was to explore whether COF may cause VAP.MethodsRetrospective clinical, microbiological and radiographic analysis of all prospectively collected suspected VAP cases in which bronchoalveolar lavage fluid exclusively yielded ≥ 104 cfu/ml COF during a 9.5-year period. Characteristics of 899 recent intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…VAP is caused by tracheal intubation and MV as a result of the disappearance of the natural barrier between the oropharynx and the trachea, resulting in bacteria-laden oropharyngeal secretions to be inhaled into the lungs. 38 According to Scholte et al, 54 commensal oropharyngeal flora appear to be a potential cause of VAP in ICU patients. In airway secretion culture-positive bacterial classifications, we found that probiotics appeared to reduce infection with GN and MDR bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…VAP is caused by tracheal intubation and MV as a result of the disappearance of the natural barrier between the oropharynx and the trachea, resulting in bacteria-laden oropharyngeal secretions to be inhaled into the lungs. 38 According to Scholte et al, 54 commensal oropharyngeal flora appear to be a potential cause of VAP in ICU patients. In airway secretion culture-positive bacterial classifications, we found that probiotics appeared to reduce infection with GN and MDR bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, culture samples reported as RTF had more in common with C+ samples than with C-, suggesting that they may represent a higher risk for pneumonia (as currently defined clinically) in this patient cohort. Along these lines previous examinations of commensal oral flora (by traditional culture methods) have been associated with the development of VAP in the ICU [ 34 ]. This may warrant considering whether patients with bacteria designated as RTF should be clinically treated similar to patients who are C+.…”
Section: Discussionmentioning
confidence: 92%
“…The relative abundance of bacteria in the RTF samples was often dominated by two to three bacterial genera. These genera are often considered clinically significant and commensal oral flora has been associated with the development of VAP, especially in immunocompromised individuals [ 34 ]. However, given the mix of genera that comprise the RTF, and their lower levels of CFUs, patients with RTF are often not treated with antibiotics to resolve the bacterial growth.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the original version of this article [ 1 ] contained an error. The title was stated incorrectly.…”
Section: Erratummentioning
confidence: 99%